Educational Empowerment of Women: A Major Tool in the Achievement of Millennium Development Goals of Reduction of Maternal and Child Mortality in Nigeria (2007)
Maternal and Child Mortality have remained issues of great concern in developing countries as effort to reduce them has not yielded much result. To achieve millennium development goals of reducing maternal and child mortality, issues of maternal education must he addressed. Educational empowerment enables women to utilize maternal health services, in order to maintain a healthy reproductive life and to bring up healthy children. This paper is based on findings from a study carried out in Akinyele local government in Oyo State. Nigeria. The study revealed that many of the women had low educational status and they utilized more of the services from the Traditional Birth Attendants (TBAs) and church. Also educational status had association with utilization of Prenatal, Delivery, Postnatal and Family Planning services. Also, women with higher level of education were in better position to make independent decisions concerning their health and that of their children.